Correction: The gut microbiota mediates the protective effects of anserine supplementation on hyperuricaemia and associated renal inflammation. Issue 2 (6th January 2022) - Han, Jiaojiao; Wang, Ziyan; Lu, Chenyang; Zhou, Jun; Li, Ye; Ming, Tinghong; Zhang, Zhen; Wang, Zaijie Jim; Su, Xiurong
Abstract : Correction for 'The gut microbiota mediates the protective effects of anserine supplementation on hyperuricaemia and associated renal inflammation' by Jiaojiao Han et al., Food Funct., 2021, 12, 9030–9042, DOI: ; 10.1039/D1FO01884A .